Unveiling the Redox Control of Plant Reproductive Development during Abiotic Stress - Zinta, Gaurav; Khan, Asif; AbdElgawad, Hamada; Verma, Vipasha; Srivastava, Ashish Kumar (Frontiers in Plant Science, 2016)
Unveiling the redox control of plant reproductive development during abiotic stress